Pengaruh Total Quality Management (Tqm) Dan Self Efficacy Terhadap Kinerja Karyawan Pt. Bakrie Sumatera Plantations Tbk Kisaran - Kartika Sahara; Febyo Angela (Cattleya Darmaya Fortuna, 2025)
The advancement of a company or organization is highly dependent on the quality of its human resources. The term